Tree Preservation Order (TPO) Act 172 and the property owners land value: a preliminary review / Mohammad Fitry Md Wadzir ... [et al.] - Md Wadzir, Mohammad Fitry; Aliasak, Mohd Hasrol Haffiz; Sa’ad, Mohd Farid; Azman, Najma; Mohamad @ Masri, Muhammad Hilmi (Universiti Teknologi MARA, Perak, 2025)
Trees are vital to our existence that helps balance the demands of the environment and human needs. Due to urban area's rapid development, trees are being cut down and causing environmental problems. The Town and Country Planning Act of 1976 established the Tree Preservation Order (TPO), which the preservation of trees in Peninsular Malaysia. Although this type of restriction is more advantageous to society overall, it negatively affects property values and causes suffering for landowners. Thus, this paper aims to explore the Tree Preservation Order (TPO) and the property owners right regarding land value against Tree Preservation Order that local governments have gazette in accordance with the Town and Country Planning Act of 1976. The purpose of this study is to ascertain the value of Tree Preservation Order (TPO) in urban areas as well as the effects on property owners land value in relation to implementation of Tree Preservation Order (TPO). The literature from journals and publications was extensively read in order to conduct this study. The literature reviews highlight how crucial it is to preserve trees because doing so will lessen their negative effects on the ecosystem and related to the land value can be expounded. This study may widen public and property owner knowledge about the granting of Tree Preservation Orders (TPO) and raise local government awareness of the value of tree preservation and the readiness to provide compensation rights if the public demand it.